The Description of Knowledge and Attitude of Coffee Lovers on Diabetes Melitus At Coffee Shops In Palaran District: The Description of Knowledge and Attitude of Coffee Lovers on Diabetes Melitus At Coffee Shops In Palaran District - Ma'ruf, Muhammad; Setianto, Arif Budi; Lasanudin, Rindi Ibrahim; Yuliani, Sapto (Universitas Widya Gama Mahakam Samarinda, 2023)
Background: Diabetes mellitus is a disease that is often called